2020
DOI: 10.31646/gbio.69
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak Situation in Nigeria and the Need for Effective Engagement of Community Health Workers for Epidemic Response

Abstract: The current Coronavirus Disease (COVID-19) outbreak has affected over 200 countries including Nigeria. It is one of the largest respiratory disease outbreaks affecting several countries simultaneously and a novel strain of Coronavirus (SARS-CoV 2) has been identified as the causative agent. Sequel to the advice of the International Health Regulation Emergency Committee, the Director-General of WHO declared the COVID-19 outbreak a Public Health Emergency of International Concern (PHEIC) on 30 January 2020 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…In all, 1,241 women participated in the study. Their ages ranged from 17-49 years with median age (IQR) of 31 years (28)(29)(30)(31)(32)(33)(34)(35)(36). Almost all (93.31%) were married and most had secondary education (50.28%), were employed (81.71%) and perceived their health to be good (50.68%) [Table 1].…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…In all, 1,241 women participated in the study. Their ages ranged from 17-49 years with median age (IQR) of 31 years (28)(29)(30)(31)(32)(33)(34)(35)(36). Almost all (93.31%) were married and most had secondary education (50.28%), were employed (81.71%) and perceived their health to be good (50.68%) [Table 1].…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Many countries such as Kenya, Liberia and Rwanda have started leveraging CHWs for COVID-19 infection prevention, case detection and response ( Ajisegiri et al , 2020 ). Identification of cases that exhibit COVID-19 symptoms or non-compliance of preventive measures has been shown to flag and interrupt community transmission at an earlier stage ( Ajisegiri et al , 2020 ). Contact tracing initiatives focus primarily on reducing the risk of disease transmission, and access to support (such as food, medicine and hygiene supplies) so effective quarantine/isolation practices are adhered with.…”
Section: Outreach and Community Engagementmentioning
confidence: 99%
“…clinical) needed for effective contact tracing, contact tracing efforts are only effective to the degree to which affected individuals are willing to pick up the phone and be contact traced. Effective rapid outbreak containment has been linked with mobilization activities that have garnered trust between health workers and the communities that they serve ( Ajisegiri et al , 2020 ). The existing distrust within Black and Latinx communities of the health care system, combined with well-documented access and quality of care problems, render CHWs a more suitable workforce for this component of pandemic response.…”
Section: Outreach and Community Engagementmentioning
confidence: 99%
“…Adegboye et al [6] dealt with early spread of COVID-19 in Nigeria. Ajisegiri et al [9] analyzed the outbreak scenario of COVID-19 in Nigeria. Researchers in different areas have presented excellent research on preventive and curative steps to contain the pandemic and have reported better outcomes.…”
Section: Introductionmentioning
confidence: 99%